2015
DOI: 10.21149/spm.v57i5.7621
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for extended-spectrum b-lactamases-producing Escherichia coli urinary tract infections in a tertiary hospital

Abstract: Objective. To assess the risks factors for urinary tract infections (UTIs) caused by Extended-Spectrum Beta-Lactamases (ESBLs)-producing E. coli and the molecular characterization of ESBLs. Materials and methods. A case-control study was performed to identify risk factors in consecutively recruited patients with UTIs caused by ESBLs or non-ESBLs-producing E. coli in a tertiary hospital in Mexico. Results. ESBLs-producing E. coli were isolated from 22/70 (31%) patients with E. coli UTIs over a three month perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
5
8
1
1
Order By: Relevance
“…The ESBL producer E. coli was implicated in community and hospital acquired infection and thus limited the treatment options of the infections induced by such bacteria [26]. The extent of resistance rate that was demonstrated in this study of ESBL E. coli isolates was consistent with previous reports [26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The ESBL producer E. coli was implicated in community and hospital acquired infection and thus limited the treatment options of the infections induced by such bacteria [26]. The extent of resistance rate that was demonstrated in this study of ESBL E. coli isolates was consistent with previous reports [26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…ESBL positive E. coli was with significantly higher resistance rate to tetracycline and aziteonam than ESBL negative isolates. ESBL positive E. coli isolates were higher resistant to cotrimoxazole than ESBL negative isolates and this was in line of previous studies [26,30,31,32,35,36,38]. The resistance rate was significantly higher in ESBL producer E. coli than that of negative isolates to ciprofloxacin, norfloxacin and nalidixic acid of the quinolone antibiotics group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Kulkarni et al study, in 2017, in the northeast of Carnataka, the highest infection was with Escherichia coli, with an increase in resistance to ampicillin up to 82.53% and an increase in sensitivity to imipenem up to (96.71%) (30). In the Alcántar study in 2015, Escherichia coli showed the highest resistance to cephalosporin and showed the highest susceptibility to carbapenem and amikacin (29), which is contradicted with the data from our study. The cause of creating different resistance and sensitivity patterns can be the unnecessary use of antibiotics and, consequently, drug resistance.…”
Section: Discussioncontrasting
confidence: 88%
“…In the current study the ESBL producing E. coli was resistant to ciprofloxacin (100%), levofloxacin (80%), gentamycin (100%),cefotaxime (100%), trimethoprim (60%), amikacin (40%), amoxicillinclavulanic acid (40%), tazobactum+pipracilline (20%), and meropenem(0%).The most potent antibiotic was meropenem (100%).Our study correlate with the previous study that isolated ESBL producing E. coli were highly resistant to ciprofloxacin (100%) and levofloxacin (100%) and the susceptible antibiotic was meropenem (100%) [25].…”
Section: Discussionsupporting
confidence: 87%